Influence of Compliance by Knowledge Education Based Health Promotion Intervention for Patients with Cerebral Hemorrhage Hematoma Removal - Qianzhu ZHANG (康复学报)
Objective:To study the influence of compliance by knowledge education based health promotion intervention for patients with cerebral hemorrhage hematoma removal.Methods:A total of 118 patients with cerebral hemorrhage hematoma removal were selected and divided into research group and control group randomly, 59 cases in each group. The control group was given by routine nursing, while the research group was given knowledge education based health promotion intervention in the basis of the control group. Living self-care ability was assessed by Functional Independence Measure (FIM) scale standard. The differences of treatment compliance, postoperative complications incidence, living self-care ability and nursing satisfaction between two groups were compared.Results:The treatment compliance rate of the research group was significantly higher than that of the control group, while postoperative complications incidence rate was lower than that of the control group, with statistically significant difference (P<0.05). Before nursing, there was not statistically significant difference of FIM score (P>0.05) between two groups, and after nursing, FIM score of all patients were significantly higher pre-nursing, FIM score of the research group was significantly higher than that of the control group, compared with statistically significant differences (P<0.05). Nursing satisfaction of the research group was significantly higher than that of the control group, with statistically significant difference (P<0.05).Conclusion:Knowledge education based health promotion intervention can significantly improve compliance, reduce postoperative complications risk, and improve their living self-care ability and nursing quality for patients with cerebral hemorrhage hematoma removal. It is worthy of clinical popularization and application.